Carburization of Fe/Ni Catalyst for Efficient Growth of Single‐Walled Carbon Nanotubes. Issue 35 (2nd July 2019) - Lin, Dewu; Zhang, Shuchen; Liu, Weiming; Yu, Yue; Zhang, Jin
Abstract: Scale‐up production of single‐walled carbon nanotubes (SWNTs) with high quality and purity is in pursuit, since the subsequent post purification treatment of residual metal or amorphous carbon is complicated and restricts further applications. Here, a compatible method to efficiently synthesize pure SWNTs on various supporters by using the precarburized Fe/Ni catalysts is reported. The preparation of catalysts is achieved by gas phase deposition together with CO gas at proper temperature, and the carburization of metal particles occurring simultaneously contributes to the size limitation of catalysts. By using micro‐quartz sand as a recyclable supporter, high‐quality SWNTs with a yield of 50 mg h −1 are prepared with 60% metal precursor utilization, 81% carbon source utilization, and only 0.12% (m/m) metal residues. Taking advantage of carburized Fe/Ni catalysts and appropriate supports makes it possible to balance the quantity, purity, and quality among SWNTs growth. Furthermore, this method provides a straightforward pathway to strongly combine SWNTs and diverse composite materials for further potential applications. Abstract : Single‐walled carbon nanotubes (SWNTs) are efficiently synthesized on various supporters by carburized Fe/Ni catalysts. The precarburization treatment restrains the aggregation of metal catalysts to a great extent. By using micro‐quartz sand as supporters, high‐quality SWNTs are fabricated with 60% metal precursor utilization, 81% carbon source utilization, and only 0.12% (m/m) metal residues.